Developing Genially Learning Media for Automotive Technical Students - Hanifah Dwi Nur Abibah (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research focuses on the development of interactive learning media using Genially to improve students’ mastery of automotive vocabulary in a vocational high school setting. The study is driven by the need for engaging and accessible learning resources that effectively support the understanding of tools, components, and safety equipment used in the workshop. The Research and Development (R&D) approach with the ADDIE model follows a five-stage process which includes Analysis, Design, Development, Implementation, and Evaluation. The analysis stage requires a semi-structured interview with an English teacher to determine what students need to learn. The design stage requires the organization of workshop manual content and validated materials into specific categories. The development stage requires the creation of Genially-based content, which includes interactive elements such as clickable images and quizzes, and multimedia features to enhance student engagement and vocabulary retention.
Reuploud file repositori 28 Januari 2026_Yudi
Keywords: eveloping Genially Learning Media; Automotive Technical Students